PERTANGGUNGJAWABAN PERUSAHAAN INDUK TERHADAP PERUSAHAAN ANAK DALAM HAL TERJADINYA PENCEMARAN DAN/ATAU KERUSAKAN LINGKUNGAN HIDUP - Miranda Chairunnisa; Alvi Syahrin; Tan Kamello; Mahmul Siregar (Universitas Sumatera Utara, 2013)
Group corporation as one of the effects of the fast growing economy, in the activities can also play a role in terms of pollution and/or environmental damage done by one or several subsidiaries. In this regard, the parent corporation may be subject to liability in certain cases where there is contamination and/or damage to the environment done by the subsidiary. Based on the results of research, it can be seen that the legal relationship between the parent corporation to the subsidiaries is the employment relationship or other relationship within the scope of work of the enterprise. The parent corporation may be subject to civil liability for pollution and/or environmental damage done by the subsidiary if the parent corporation controls the subsidiaries proven to perform actions within the scope of application of piercing the corporate veil. In addition, the parent corporation may also incur criminal liability if it is proved the parent corporation were also committing a crime of pollution and/or environmental damage done by the subsidiary. Based on this research, it is advisable to make a special provision of group companies in Limited Company Act. In addition, it should be prioritizing the use of criminal law in a law enforcement environment that affects the survival of human beings, as well as the need to increase the moral of businessmen for committing violations of environmental laws.